THE PRICE CHANGES OF BASIC NEEDS ON THE POVERTY LEVEL - Indra Maipita; Fahrurrozy Fahrurrozy; Setyo Tri Wahyudi; Fitrawaty Fitrawaty (Faculty of Economics and Business, University of Pasundan, 2020)
Poverty is often identified in developing countries. One measure of poverty is the ability to fulfill basic needs, particularly food needs. On the other hand, food needs are very sensitive to changes in inflation. The more fluctuating inflation will change the prices of necessities, which then exacerbate poverty conditions. Using time-series data for the period 2005-2016 and using the Ordinary Least Square method, this study examines the impact of changes in the prices of necessities on poverty levels in North Sumatra. The results showed that the increase in rice prices, sugar, cooking oil, beef, and salt had an impact on the poverty level in North Sumatra, while the increase in the price of eggs and kerosene was the opposite. The increase in rice prices significantly impacted all of the commodities studied than for other commodities, followed by salt, sugar, beef, and cooking oil. Changes in the ability to consume basic needs indicate a decrease in people's purchasing power. Further, this indicates that the change in consumption of these various commodities also means that the poverty rate tends to increase.